Incidence of Radioembolization-Induced Liver Disease and Liver Toxicity Following Repeat 90Y-Radioembolization: Outcomes at a Large Tertiary Care Center. (February 2020) - Elsayed, Mohammad; Ermentrout, Robert M.; Sethi, Ila; Bercu, Zachary L.; Galt, James R.; Whitmore, Morgan; Brandon, David C.; Schuster, David M.; Kokabi, Nima
Abstract : Purpose: The complication profile following repeat 90 Y-radioembolization (RE) is not well understood, and repeat RE is sometimes avoided because of concerns for RE-induced liver disease (REILD) and liver toxicity. The purpose of this study was to examine the incidence of REILD and liver toxicity following repeat 90 Y-RE and to identify potential risk factors. Methods: A retrospective analysis of patients undergoing repeat RE to the same hepatic lobe between 2013 and 2018 was performed. Baseline factors were evaluated as predictors of liver toxicity, mortality, and REILD, which was defined as the presence symptomatic ascites or jaundice in the absence of biliary obstruction within 8 weeks following RE. Post-RE complications were graded according to the Common Terminology Criteria for Adverse Events version 5. Results: A total of 39 patients underwent repeat RE with 14 (35.9%) experiencing Common Terminology Criteria for Adverse Events toxicity of grade 2 or greater, 3 (10.3%) grade 3, and no grade 4 or greater. A Model for End Stage Liver Disease score of 8 or greater was associated with grade 2 toxicity or greater (26.7% vs 75%; P = 0.013). Only 3 patients (7.7%) experienced REILD due to symptomatic ascites without jaundice. Greater than 2 REs were associated with a greater rate of 6-month mortality (12% vs 58.3%, P = 0.003), 12-month mortality (28% vs 75%, P = 0.007), and REILD (0% vs 21.4%, P = 0.016). Age, sex, microsphere type, cirrhosis, Child-Pugh, and Eastern Cooperative Oncology Group status were not significantly associated with complications, REILD, or survival. Conclusions: Repeat 90 Y-RE appears to be well tolerated with a low rate of high-grade adverse events and REILD.